HUBUNGAN PERAN BIDAN PADA PELAKSANAAN INISIASI MENYUSUI DINI (IMD) DALAM PERSALINAN DENGAN PROGRAM IMD PADA IBU BERSALIN DI RUMAH SAKIT WILAYAH KOTA PEKALONGAN - Diah Atmarina Yuliani (Universitas Duta Bangsa Surakarta, 2020)
Early initiation of breastfeeding (IMD) and so for the baby. Babies breastfed for 1 hour or more on the mother's chest immediately after birth. Implementation of the IMD on maternal need midwives’s role to IMD programs can work as expected. This study aims to determine the relationship of the midwife's role in the implementation of Early Initiation of Breastfeeding (IMD) in the Maternity with Implementatiton Early Initiation of Breastfeeding Program to Maternal in Regional Hospital Pekalongan City. Study used descriptive correlative with cross sectional approach. Samples were midwives in Regional Hospital Pekalongan City as many as 53 peoples. Sampling technique used total sampling. Collecting data used a questionnaire. Results of univariate analysis showed that midwife’s role in the implementation Early Initiation of Breastfeeding (IMD) that 31 (58.3%) was enough and Early Initiation of Breastfeeding (IMD) Program on maternal that 37 (69.8%) was not implemented. Spearman rank correlation test results showed that there was relationship of the midwife’s role to implementation Early Initiation of Breastfeeding (IMD) in the maternity with implementation Early Initiation of Breastfeeding Program to maternal in regional hospital Pekalongan City with ρ value 0.006 <0.05. Correlation spearman rank was 0,374 which means the relationship exactly. For midwives who have sufficient role should increase skill early breastfeeding initiation in the implementation of the IMD and midwife training should undertake delivery care in accordance with the operational standards specified as APN.